A Novel Multiple-Output DUSTF Coding on High Mobility MIMO-Wireless Communication Systems - Rina Pudji Astuti; Andriyan B. Suksmono; Sugihartono Sugihartono; Adit Kurniawan (Journal of ICT Research and Applications, 2008)
In the future, wireless access system will operate in high data rate transmission and high mobility environment, to support private and public access. For such an environment, it is necessary to develop a system that has a higher spectrum efficiency and is able to mitigate selective fading problems. A novel multiple-output differential unitary space-time frequency (DUSTF) coding scheme is proposed to overcome those problems. The implementation of this inner coding scheme is unified with MIMO system, so that the scheme has a good spectrum efficiency. The differential space-time modulation in this proposed scheme is intended to operate in a non-coherent channel transmission scheme and to guarantee the system performance. In order to combat the selective fading problems, the multi-carrier space frequency scheme is utilized in the proposed scheme. In general, simulation result shows that the MIMO wireless system with the multiple-output DUSTF coding scheme in a non-coherent channel transmission scheme provides a good system performance. The proposed scheme can outperforms other previously published inner coding scheme for high mobility and high SNR. The system also achieves a good channel capacity.